2015
DOI: 10.1021/acs.macromol.5b01737
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity Studies of Alkoxy-Substituted [2.2]Paracyclophane-1,9-dienes and Specific Coordination of the Monomer Repeating Unit during ROMP

Abstract: The polymerization of alkoxy-substituted [2.2]-paracyclophane-1,9-dienes via ring-opening metathesis polymerization (ROMP) to obtain soluble poly(pphenylenevinylene)s is a versatile method due to its living nature which enables the possibility of block copolymerization and end group modification. However, detailed studies on the reactivity behavior and the polymerization process of alkoxysubstituted [2.2]paracyclophane-1,9-dienes have not been reported so far. Herein we present a detailed study on the varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 54 publications
1
39
0
Order By: Relevance
“…25,31 This was a consequence of the oxygen atom in the ortho position of the benzylidene ring coordinating to the ruthenium metal displacing the tricyclohexylphosphine. 32 This strong interaction leads to a reduced rate of propagation and has recently been observed for similarly substituted cyclophanedienes by Zentel et al 28 The [2.2]paracyclophane--1,9--dienes; M1, M2 and M3 are substituted with n--octyl chains and therefore no coordination of the side chains to the ruthenium metal is possible. Initially the ROMP of M1 was initiated with Grubbs second generation catalyst (G2) with a [M1]/[G2] of 10/1, using THF as a solvent at 40 °C, followed by quenching of the reactive ruthenium carbene chain end with ethyl vinyl ether.…”
Section: Poly(p--phenylenevinylene--25--dioctyl--p--phenylenevinylene)smentioning
confidence: 75%
See 1 more Smart Citation
“…25,31 This was a consequence of the oxygen atom in the ortho position of the benzylidene ring coordinating to the ruthenium metal displacing the tricyclohexylphosphine. 32 This strong interaction leads to a reduced rate of propagation and has recently been observed for similarly substituted cyclophanedienes by Zentel et al 28 The [2.2]paracyclophane--1,9--dienes; M1, M2 and M3 are substituted with n--octyl chains and therefore no coordination of the side chains to the ruthenium metal is possible. Initially the ROMP of M1 was initiated with Grubbs second generation catalyst (G2) with a [M1]/[G2] of 10/1, using THF as a solvent at 40 °C, followed by quenching of the reactive ruthenium carbene chain end with ethyl vinyl ether.…”
Section: Poly(p--phenylenevinylene--25--dioctyl--p--phenylenevinylene)smentioning
confidence: 75%
“…35 Conversely, Zentel et al found that reducing the alkoxy chain length to a methoxy group and refluxing in toluene resulted in polymerisation of the pseudo--ortho isomer. 28 ROMP of the mixture of M2 and M3, was initiated with G3, assuming that only M2 is reactive towards metathesis. An initial [M2]/[G3] ratio of 10/1 was used and the polymerisation was quenched by the addition of ethyl vinyl ether, after complete monomer conversion (Scheme 2).…”
Section: Poly(25--dioctyl--p--phenylenevinylene)smentioning
confidence: 99%
“…All the before mentioned polymerization protocols to obtain PPV and derivatives follow typical polycondensation kinetics, with poor control of molecular weight and polydispersities. More recently, routes utilizing the ring opening metathesis polymerization (ROMP) of cyclophanedienes as strained monomers are able to afford PPVs with controlled molecular weights; this strategy can clearly pave the way to the production of block/alternating PPV‐like copolymers , and it has refreshed scientific attention towards this class of conjugated polymers.…”
Section: Resultsmentioning
confidence: 99%
“…11 The high ring strain of this class of molecules, calculated to be 176 kJ mol −1 for cyclophanediene 1, makes them interesting monomers in polymer science. [14][15][16][17][18] These conjugated polymers have been extensively studied for application in electronic and optoelectronic devices, and recently in fluorescence imaging. [14][15][16][17][18] These conjugated polymers have been extensively studied for application in electronic and optoelectronic devices, and recently in fluorescence imaging.…”
Section: Introductionmentioning
confidence: 99%